METHODOLOGY FOR THE DEVELOPMENT OF DIGITAL COMPETENCE OF SCIENTIFIC AND SCIENTIFIC-PEDAGOGICAL STAFF USING THE CANVA GRAPHIC DESIGN WEB SERVICE (Journal of Information Technologies in Education (ITE), 2025)
The article presents the author's methodology for developing the digital competence of scientific and scientific-pedagogical staff using the Canva graphic design web service. The relevance of the study is due to the need to improve the digital skills of education and science staff in the context of digitalization. The Canva web service is considered an effective didactic tool for developing the digital competence of scientific and scientific-pedagogical staff, visualizing knowledge, supporting academic communication, and creating interactive content. The conceptual principles of digital competence are substantiated in accordance with national and European frameworks (DigComp, DigCompEdu, DigComp 2.2, the National Framework for Digital Competence of Citizens of Ukraine, the Conceptual and Reference Framework for Digital Competence of Pedagogical and Scientific-Pedagogical Workers), and an analysis of modern research on the implementation of digital platforms in education is conducted. It is determined that the digital competence of scientific staff and university teachers, according to the types of professional activity, includes educational, research, methodological, organizational and communication, and cross-functional components. As part of the study, a two-module special course was developed, focused on the development of digital competence of scientific and scientific-pedagogical staff using Canva tools. The correspondence of the platform's functionality to each of the components of digital competence was analyzed: creating graphic materials, working with templates, interactivity, collaboration, and compliance with copyright. The proposed methodology includes the goal, forms, methods, tools, a two-module special course that combines theoretical knowledge with practical skills in creating presentations, infographics, posters, and other elements of visual design. The methodology is based on the principles of interactivity, consistency, accessibility, and practical orientation. It is shown that the use of Canva contributes to increasing the effectiveness of academic communication, developing teamwork skills, and forming creative thinking. Prospects for further research are outlined, in particular, regarding the adaptation of the methodology to various educational contexts and expanding methodological support. Prospects for further research include testing the effectiveness of the developed methodology in scientific institutions and universities.
Keywords: digital competence; scientific and scientific-pedagogical staff; methodology; Canva web service; components; special course; higher education institutions; scientific institutions